Pengembangan Kurikulum Merdeka Belajar – Kampus Merdeka (MBKM) pada Perguruan Tinggi Keagamaan Islam (PTKI) - Ria Rizki Ananda; Ahmad Suradi; Dwi Ratnasari (ISLAMIKA, 2022)
Today change is taking place so rapidly following the currents of globalization and technological advances. Therefore, education has an important role in preparing Human Resources (HR) who have a variety of skills in order to face a dynamic life. The Merdeka Belajar Policy – Kampus Merdeka is here to improve the competence of graduates from universities in the form of soft skills and hard skills in order to adjust to the needs of the times. In this study, the type of research used is library research. The data collection used is the documentation method. The MBKM policy includes four main policies, namely: ease of opening new study programs, changes in the higher education accreditation system, the ease of universities becoming legal entities, and the right to study three semesters outside the study program. Learning activities outside the study program and outside of higher education include internships, rural projects, teaching in schools or madrasah, student exchanges, research, entrepreneurship, independent projects, and humanitarian projects. Broadly speaking, curriculum development has three stages, namely the curriculum design stage, learning implementation, and learning evaluation.